Depletion of Ground Water in District Gurugarm (Haryana): Understanding the challenges of groundwater depletion in Gurugram, Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Groundwater, the nature's valuable blessing, once accepted to be unlimited source of water, is currently ending up more rare and rare in urban and in rural areas. Groundwater is a vital source of water for household, horticultural, and industrial prerequisites. Because of intrusion by sewage depletes and drains, a large portion of the surface water sources can't serve perfect and safe water. In the present setting of water supply, groundwater is accepted to be the most dependable source of water and vast number of clients seeks this constrained source of water. Water shortage is turning into an expanding issue over the world, with 35 of the worldwide land surface being semi-dry (Stanger, 1995). In 1997, it was accounted for that roughly 80 of nations experience the ill effects of genuine water deficiencies, which incorporates 40 of the total populace (Nigam et al., 1997).